MAPPING OF SOCIAL AND PUBLIC FACILITY BASED ON GEOGRAPHY INFORMATION SYSTEM (Studi Kasus di DKI Jakarta) - Ikasari, Diana (Jurnal Ilmiah Informatika Komputer, 2009)
Rapid development of the City of Jakarta were followed by increased population. This phenomenon have an effect of creating more unfortunate people. As a consequence, the Local Government of Jakarta requires to build more social and public facilities. Therefore, informaton system becomes very important to provide information to public regarding the location of the facilities. The system is based-on Geographic Information System (GIS). This system assists the Local Government in planning the city development as well as facilitate user for searching social and public facilities.Keyword(s): Mapping, Social facility, Public facility, Geographic information system.Subject Description : H. Information Systems | H.4 Information Systems Applications | H.4.2 Types of Systems | Decision support